Some Remarks on State Immunity and Professor Wolfke’s Concept of International Customary Law - Wyrozumska, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The contribution deals with some recent examples of identification of customary international law on State immunity by international and domestic courts and confronts some of their aspects with Professor Wolfke`s understanding of customary international law.
Keywords: immunitet państwowy; prawo zwyczajowe; wniosek sądowy